2021
DOI: 10.1038/s41467-021-21675-6
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations and single-cell transcriptomes reveal the root of malignant rhabdoid tumours

Abstract: Malignant rhabdoid tumour (MRT) is an often lethal childhood cancer that, like many paediatric tumours, is thought to arise from aberrant fetal development. The embryonic root and differentiation pathways underpinning MRT are not firmly established. Here, we study the origin of MRT by combining phylogenetic analyses and single-cell mRNA studies in patient-derived organoids. Comparison of somatic mutations shared between cancer and surrounding normal tissues places MRT in a lineage with neural crest-derived Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 54 publications
1
60
0
Order By: Relevance
“…Indeed, we observed a mutation in oncogene MYC and a subclonal deletion of a part of chromosome 18 in the matching clonal iPSC cell line . Nevertheless, during fetal development and even during early embryogenesis, cells can also acquire oncogenic mutations ( Custers et al., 2021 ; Greaves, 2018 ; Williams et al., 2020 ). For example, sacrococcygeal teratomas, the most common tumor type in newborns, arise from germ cells and can recapitulate cells of all three germ layers ( Manes, 1976 ; Moore et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we observed a mutation in oncogene MYC and a subclonal deletion of a part of chromosome 18 in the matching clonal iPSC cell line . Nevertheless, during fetal development and even during early embryogenesis, cells can also acquire oncogenic mutations ( Custers et al., 2021 ; Greaves, 2018 ; Williams et al., 2020 ). For example, sacrococcygeal teratomas, the most common tumor type in newborns, arise from germ cells and can recapitulate cells of all three germ layers ( Manes, 1976 ; Moore et al., 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, RMS tumoroid models are less intricate in their propagation. Lastly, while GEMs are considered essential for cell of origin studies, recent advances have shown that by genetic editing, such studies can now also be performed in tumoroid models (Custers et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 74 Custers et al discovered that combined HDAC and mTOR inhibition mimics MRT differentiation. 75 Recently, a small molecule epigenetic modulator known as domatinostat (4SC-202), inhibiting both class I HDACs and Lysine Demethylase (LSD1) was investigated, and cytotoxic and cytostatic effects on malignant rhabdoid tumor cells were detected. 76 The histone deacetylase inhibitor, OBP-801 induced apoptosis in malignant rhabdoid tumor cells by epigenetically releasing the silencing of NOXA, a key mediator of MRT apoptosis.…”
Section: Potential Targeted Therapeutic Approaches To Extracranial Mrtmentioning
confidence: 99%